A Scoping Review on the Usage of AI-Based Hiring Systems on South Africa - Melanie Elisabeth Lourens; Samuel Bangura (International Research Journal of Business Studies, 2026)
Artificial intelligence (AI)-based hiring systems are rapidly transforming recruitment and talent acquisition practices across the globe. This scoping review examines the extant literature on AI-based hiring systems with a particular focus on the South African context, exploring adoption patterns, ethical challenges, legal implications, and organisational outcomes associated with algorithmic recruitment. Guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) framework, the review synthesises 52 peer-reviewed articles, reports, and policy documents published predominantly between 2022 and 2025. Findings reveal that while AI-based hiring tools offer demonstrable efficiencies in candidate screening, predictive assessment, and bias reduction under controlled conditions, their deployment in South Africa is complicated by intersecting structural inequities, including persistent digital divides, algorithmic bias reflecting historical exclusion, and inadequate regulatory frameworks. The review identifies four thematic clusters: (1) the landscape of AI adoption in South African hiring; (2) algorithmic fairness and bias in heterogeneous labour markets; (3) legal and ethical governance gaps; and (4) organisational and candidate experience outcomes. The paper concludes with a synthesis of lessons for practitioners, policymakers, and researchers, advocating for context-sensitive AI governance, inclusive system design, and robust human oversight mechanisms tailored to the unique socio-economic conditions of sub-Saharan Africa